Genome‐wide analysis of primary plasma cell leukemia identifies recurrent imbalances associated with changes in transcriptional profiles12. Issue 1 (9th October 2012) - Mosca, Laura; Musto, Pellegrino; Todoerti, Katia; Barbieri, Marzia; Agnelli, Luca; Fabris, Sonia; Tuana, Giacomo; Lionetti, Marta; Bonaparte, Eleonora; Sirchia, Silvia Maria; Grieco, Vitina; Bianchino, Gabriella; et al.
Abstract Primary plasma cell leukemia (pPCL) is a rare, yet aggressive form of de novo plasma cell tumor, distinct from secondary PCL (sPCL) which represents a leukemic transformation of pre‐existing multiple myeloma (MM). Herein, we performed a comprehensive molecular analysis of a prospective series of pPCLs by means of FISH, single nucleotide polymorphism (SNP) array and gene expression profiling (GEP). IGH@ translocations were identified in 87% of pPCL cases, with prevalence of t(11;14) (40%) and t(14;16) (30.5%), whereas the most frequent numerical alterations involved 1p (38%), 1q (48%), 6q (29%), 8p (42%), 13q (74%), 14q (71%), 16q (53%), and 17p (35%). We identified a minimal biallelic deletion (1.5 Mb) in 8p21.2 encompassing the PPP2R2A gene, belonging to a family of putative tumor suppressors and found to be significantly down‐regulated in deleted cases. Mutations of TP53 were identified in four cases, all but one associated with a monoallelic deletion of the gene, whereas activating mutations of the BRAF oncogene occurred in one case and were absent in N‐ and K‐RAS. To evaluate the influence of allelic imbalances in transcriptional expression we performed an integrated genomic analysis with GEP data, showing a significant dosage effect of genes involved in transcription, translation, methyltransferase activity, apoptosis as well as Wnt and NF‐kB signaling pathways. Overall, we provide a compendium of genomic alterations in a prospective series of pPCLs which may contribute to improve our understanding of the pathogenesis of this aggressive form of plasma cell dyscrasia and the mechanisms of tumor progression in MM. Am. J. Hematol. 2013. © 2012 Wiley Periodicals, Inc.